Biochemical and histological effects of low dose of monosodium glutamate on the liver of adult male Sprague-Dawley rats - Siti Fathiah Masre; Nur Athirah Razali; Nur Naimah Nani; Izatus Shima Taib (Penerbit Universiti Kebangsaan Malaysia, 2019)
Monosodium glutamate (MSG) is widely used as an additive in food. Excess consumption of MSG was reported to cause oxidative stress on brain, liver and renal resulted in increased production of reactive oxygen species (ROS). This study aims to determine the biochemical and histological effects of low dose MSG on the liver of adult male Sprague-Dawley rats. Animals (n = 6 per group) were randomly divided into three groups with two treatment groups: 60 mg/kg (MSG60) and 120 mg/kg (MSG120), and one control group (distilled water). The substances were administered to the rats via force feeding for 28 consecutive days. On day 29, all rats were killed, and liver tissues were biopsied for the biochemical (total protein, liver enzymes, and the status of oxidative stress) and histological analysis. The total protein appeared significantly decreased (p < 0.05) while alanine aminotransferase (ALT) and aspartate aminotransferase (AST) demonstrated a significant increased (p < 0.05) in the MSG120 treatment group as compared to the control group. Malondialdehyde (MDA) levels and the antioxidant levels of superoxide dismutase (SOD) were significantly increase (p < 0.05) in the MSG120 group as compared to the MSG60 and control groups. The histological findings revealed changes to normal liver architecture and accumulation of red blood cells in the central veins in both MSG groups. This study indicates that the MSG consumption at a dose of 120 mg/kg may ALTer the biochemical and histological parameters of the liver.